Use of Boron Compounds as Grinding Aids with Alcohol Amines and Their Effect on Portland Cement Setting Points - Murat Çallı; Erol Pehlivan (Advances in Civil Engineering)
Milling aids have been predominantly developed to increase the performance or grinding capacity of cement products, and alcohol amines have been used as grinding aids in cement grinding processes for many years. Moreover, the setting point of cement produced with grinding aids is most often changed. In this study, the effects of alkanolamines and boron compounds in different mixing amounts as grinding aids on the set point of cement were researched. Triethanolamine (TEA) and triisopropanolamine (TIPA) were used as alkanolamines and boric acid (BA) and anhydrous borax (AHB) as the boron compounds. It is evident that BA with TEA had a small effect on the cement setting point where the former decreased the retarding effect of the latter, but BA had no effect with TIPA. AHB decreased the retarding effect of TEA but had no effect with TIPA on setting times. When the boron compounds were added to TEA, they accelerated the initial setting points of cement by 15 to 20 minutes and the final setting points by 25 to 30 minutes according to the amount of TEA used.